Association Between Trust and Mental, Social, and Physical Health Outcomes in Veterans and Active Duty Service Members With Combat-Related PTSD Symptomatology - Kopacz, Marek S.; Ames, Donna; Koenig, Harold G. (Frontiers in Psychiatry, 2018)
Background: Trust represents a complex emotion and interpersonal concept which assumes abandoning control over a given situation or set of circumstances, in turn yielding such control to another party. Advances in our knowledge of post-traumatic stress disorder and moral injury have underscored the need to more closely examine how trust stands to impact health outcomes in these disorders. The aim of the present study is to examine and identify relationships linking general trust with select health outcomes in a mixed sample of Veterans and Service members with a self-reported history of deployment to a combat theater and PTSD symptomatology. Methods: This study applied a cross-sectional methodology, surveying n = 427 participants recruited across six sites, including 373 Veterans and 54 active duty Service members. Measures included demographic characteristics, combat exposure, general trust, post-traumatic stress disorder symptomatology, depressive/anxiety symptomatology, alcohol use, social involvement, religiosity, and physical health. Data were analyzed descriptively as well as using Pearson correlations, Student’s t-test, and multivariate regression. Results: Several significant relationships were identified, indicating an inverse relationship between trust and PTSD, depressive, and anxiety symptomatology. Greater levels of trust were also significantly associated with increased social interaction and religiosity. Lastly, no significant associations were identified with either physical functioning or pain level. Conclusion: The findings suggest that trust plays an important role in a variety of health outcomes in Veterans and Service members affected by combat-related PTSD. Additional, hypothesis-driven research, informed by longitudinal data, is needed to better understand how trust stands to impact health outcomes, including the development of strategies and intervention options for repairing trust.